Regulation of the mitochondrial ATP synthase in intact rat cardiomyocytes. - Das, A M (1990)
The ATP synthase capacity of rat heart myocytes can be measured in sonicated cell suspensions and in sonicated preparations of cultured cardiomyocytes. This procedure allows the rapid measurement of mitochondrial function in response to changes in the metabolic status of the cell. In cultured myocytes, transitions in ATP synthase capacity (with no detectable change in cellular ATP concentration) accompany a change to anoxia or electrically stimulated contraction (rise of 70%). These changes are reversed on returning to the original conditions. Exposure of myocytes to low pH has little effect on basal ATP synthase capacity (down to values less than pH 6), but markedly affects cellular ATP levels and the response of the cells to anoxia and reoxygenation, possibly mimicking changes seen in ischaemic heart. Similar effects are seen in suspensions of freshly prepared myocytes, but these preparations are less stable and more pH-sensitive than are cells in culture. It is proposed that mitochondria in vivo are directly regulated at the level of the ATP synthase, and that a regulator protein, the naturally occurring inhibitor protein from mitochondria, may be responsible for this regulation.